PEACEFUL COMPETITION DALAM KELUARGA BEDA AGAMA: SEBUAH ANCAMAN ATAU POTENSI? - Dewi, Subhani Kusuma (UIN Sunan Kalijaga Yogyakarta, 2013)
Peaceful Competition, a ter m introduced by Arnold Toynbee, aims to express various ways of religious practices. This concept occurs when an a priori religious consciousness meets the historical aspects of reli- gion. In such situations, people feel in the level of ‘between’ which consists of (1) a priori religious reflections of consciousness; and (2) religious practices within the context of cultural and social sphere. Both elements will be realized in the non-essential activities such as creeds, rules and worship.This article uses the above concept and analyzes both the results of interviews and observations on three interfaith marriage couples. The study concludes that there is no single model of peaceful competition in the practices of interfaith marriage. Conditions of threshold between a priori historical and religious part is related to the ‘sense of self ’ and ‘entities of other’. Thus, peaceful competition in the interfaith family might be considered as a tolerable stage within the couple relationship.